2020
DOI: 10.3389/fpsyg.2020.00668
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cognition and Balance Among Middle-Aged and Older Adults Observed Through a Tai Chi Intervention Program

Abstract: Background: Age-associated decline in cognition and balance may cause severe ability loss for daily living activities among middle-aged and older adults. The relationship between cognition and balance in this aging population remains to be explored.Objective: The present study Is exploratory in nature and aimed to examine the relationship between balance (both static and dynamic components) and global cognitive function among middle-aged and older adults through Tai Chi (TC) practice as a research avenue.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
0
13
0
5
Order By: Relevance
“…The wide range of motion of the arms, shoulders, hips, and knees in multiple directions was the main reason for the increased flexibility during the 16-week TCSB intervention training. In the previous research findings, exercise can improve balance [ 18 ]. In our study, the postintervention SLS has revealed an improvement of 32% compared with that before the 16-week TCSB intervention training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide range of motion of the arms, shoulders, hips, and knees in multiple directions was the main reason for the increased flexibility during the 16-week TCSB intervention training. In the previous research findings, exercise can improve balance [ 18 ]. In our study, the postintervention SLS has revealed an improvement of 32% compared with that before the 16-week TCSB intervention training.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on TC, TG, HDL-C, and LDL-C display a significant improvement in the 16-week TCSB intervention training. Meanwhile, physical training, for example, reduces TC, TG, and LDL-C and raises HDL-C [ 18 ]. Our results agree with those reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Burns et al ( 2010 ) reported that reduced lean body mass in AD is associated with brain atrophy and declined brain function, including cognitive performance. In this regard, a positive correlation has been reported between Montreal Cognitive Assessment (MoCA) test and fitness parameters especially muscle strength (Tolea and Galvin, 2016 ; Xiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tai-Chi Chuan (TCC) is an ancient Chinese martial art that has become a popular exercise for improving general mental and physical fitness, especially in the older population ( Penn et al, 2019 ; Xiao et al, 2020 ). From the physical exercise viewpoint, TCC focuses on dynamic weight-shifting when transitioning from double-limb to single-limb support during a series of slow, continuous movements with well-controlled body posture ( Wu et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%